Liver Research and Clinical Management 2018
DOI: 10.5772/intechopen.73735
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease, Diabetes Mellitus, and Zinc/ Zinc Transporters: Is there a Connection?

Abstract: Immune response and metabolic regulation are closely connected with each other in such a way that dysfunction could lead to a variety of metabolic diseases such as obesity, diabetes mellitus (Dm), lipid metabolism disorders, and fatty liver disorders. Combined with uncritical "sugar-based" overeating and malnutrition, these multisystem metabolic diseases expand into a global epidemic. There are correlations between a fatty liver disease and diabetic metabolism state. A fatty liver leads to insulin resistance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…A haemorrhagic stroke is mainly caused by a rupture and pathological changes in small vessels. The authors consider zinc to be a modifiable risk factor for haemorrhagic stroke, particularly in relation to the incidence of zinc deficiency in obesity and type 2 diabetes mellitus [ 57 , 58 , 59 ].…”
Section: Zinc Deficiency: Influence On Vessels Coagulation and Stmentioning
confidence: 99%
“…A haemorrhagic stroke is mainly caused by a rupture and pathological changes in small vessels. The authors consider zinc to be a modifiable risk factor for haemorrhagic stroke, particularly in relation to the incidence of zinc deficiency in obesity and type 2 diabetes mellitus [ 57 , 58 , 59 ].…”
Section: Zinc Deficiency: Influence On Vessels Coagulation and Stmentioning
confidence: 99%
“…The network diagram of the the cited literature is comprised of 249 nodes and 498 linkages, in addition,we run the burst detection function from the Burstness tab in the Control Panel in CiteSpace software. The results show that the keywords with higher frequency of occurrence include: oxidative stress (127), expression (78), zinc (60), activation (45), gene expression (43), cerebra ischemia (41), stroke (39), focal cerebral ischemia (39), cell death (38), ischemic stroke (36), gene (29), and risk (28) (as shown in Table 3). The keywords with the highest centrality among all are brain injury and damage, both of which are 0.27.…”
Section: Analysis Of Countries'contributionmentioning
confidence: 99%
“…They [36] conducted a retrospective analysis of serum zinc de ciency in 384 patients with acute subarachnoid hemorrhage, and found that 67% (n = 257) of the patients had reduced serum zinc content in the rst 7 days after the onset of the disease. Coincidentally, Zhang et al also pointed out that zinc is a modi able risk factor for hemorrhagic stroke, especially related to the incidence of zinc de ciency in obesity and type 2 diabetes [37][38][39] . Similarly, Munhsi et al [40] reported that serum zinc concentrations were also lower in stroke patients than in healthy controls, while no signi cant differences were found in copper and iron concentrations.…”
Section: Evolutions and Focuses Of Researchmentioning
confidence: 99%
“…Moreover, zinc is important in the metabolism of neurotransmitters and growth, sex, and thyroid hormones, as well as the synthesis, secretion, and storage of insulin in the Langerhans cells of the pancreas [31]. In addition, zinc has extensive roles in both the adaptive (specific) and the innate (non-specific) immune responses at multiple steps, including gene expression as well as differentiation and development of immune cells [3,32].…”
Section: Functions Of Zincmentioning
confidence: 99%
“…There is a vicious cycle. A fatty liver contributes to insulin resistance and therefore to type 2 diabetes mellitus; insulin resistance increases the fatty liver [31,84]. NASH is defined as fatty liver with a progressive development through inflammation and typical hepatocellular damage, accompanied by pericellular fibrosis that may lead to cirrhosis [2].…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%